Comparability of results from two leakage models - Souza, Erick Miranda [UNESP]; Wu, Min-Kai; Shemesh, Hagay; Bonetti-Filho, Idomeo [UNESP]; Wesselink, Paul R. (Mosby-elsevier, 2008)
Objective. The goal of this study was to check whether leakage results of the same specimens measured by 2 different leakage models are similar.Study design. Canine root canals were prepared and filled with cold gutta-percha cones and 1 of 4 sealers (20 canals for each sealer). The 80 specimens were first connected to a fluid transport model where air-bubble movement was measured. The same specimens were later connected to a glucose penetration model where the concentration of glucose was measured. In both models, a headspace pressure of 30 kPa was used to accelerate leakage.Results. In both models, 4 sealers ranked the same regarding the leakage they allowed, and a significant correlation between the results of the 2 models was confined (Spearman test coefficient = 0.65; P = .000001).Conclusion. Under the conditions of this study, leakage results of 80 specimens recorded in the fluid transport model and glucose penetration model were similar.